If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2cosx + -1cosx = 0 Combine like terms: 2cosx + -1cosx = 1cosx 1cosx = 0 Solving 1cosx = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '1'. cosx = 0 Simplifying cosx = 0 The solution to this equation could not be determined.
| 5(1-x)(1-x)-6(x*x-3x-7)=x(x-3)-2x(x+5)-2 | | G-80/4=3 | | 12-3x=-4(6x+4)-4(-5-5x) | | 90=3(b-37) | | -.95(20)+0.80x=0.30(20+x) | | s(t)=2.5t+12 | | 2(-3+5)+7x(-4)+(-1)= | | 6z+7=4z+2+z | | 7(q-83)=63 | | 12xX=310 | | -33+90-22-9= | | 8x-15=4x-1 | | 18=2k+2 | | 0=4x-33 | | 9w-45=8w-24 | | 5.7x-15.1+4.3x=6.4+11x | | 13-3x=5x+8-7x | | -4x+6+5x=14-26 | | -4/9w=1/6 | | 22x-5-12x+3=24x-6-14x+17 | | 21-1=51 | | 7(x-4)(x-4)-3(x+5)(x+5)=4(x+1)(x-1)-2 | | 12z=9z-8z+2z | | 8x-35=6x-9 | | 4q-17=44 | | 5y-6+y+34=5y+40-3y | | 45=2x-2 | | 13y=12y-2/3 | | 9x+15+14-50=180 | | Y-3/1-y=3 | | 5.8+1.2x=2.2x | | -0.6w-17=0.1w+2.5 |